Effects of early rehabilitation on functional outcomes in patients after coronary artery bypass graft surgery: a randomized controlled trial. Issue 3 (March 2022) - Han, Peipei; Yu, Hairui; Xie, Fandi; Li, Ming; Chen, Xiaoyu; Yu, Xing; Li, Jing; Liu, Xiangjing; Shao, Bohan; Liu, Jianjun; Liu, Yaping; Liu, Zhigang; et al.
Objective: This study evaluated the effectiveness, feasibility, and safety of early rehabilitation for patients after coronary artery bypass graft (CABG) surgery. Methods: In a three-arm randomized controlled trial, patients who underwent CABG from January 2018 to June 2018 were randomly assigned to one of three groups: (i) usual care (UC group); (ii) UC + single general ward rehabilitation (SGR group); and (iii) UC + general ward rehabilitation and intensive care unit (ICU) rehabilitation (IGR group). The primary outcome was the Barthel Index scores. Results: The Barthel Index score for UC (75.3 ± 12.1) was significantly lower than that of both SGR (86.2 ± 14.1) and IGR (89.1 ± 15.5). There was no significant difference in the Barthel Index scores between the SGR and IGR groups. Statistically significant differences were found in the length of ICU stay and post-operative hospital stay but not in post-operative pulmonary complications (PPC) or atrial fibrillation between the three groups. Conclusion: Early rehabilitation implemented during ICU stay and on the general ward resulted in significant improvements in functional independence and could be a safe part of routine care post-CABG.